Coaxial oblique interface shearing: tunable generation and sorting of double emulsions for spatial gradient drug release. Issue 7 (4th March 2020) - Huang, Fangsheng; Zhu, Zhiqiang; Niu, Ye; Zhao, Yi; Si, Ting; Xu, Ronald X.
Abstract : We propose a coaxial oblique interface shearing (COIS) process to one-step generate and sort double emulsions for thermal- and chemical-responsive spatial gradient releases. Abstract : We propose a coaxial oblique interface shearing (COIS) process for one-step generation of double emulsions which are synchronously sorted with spatial gradient distributions. As a coaxial needle supplying the inner and outer liquids obliquely vibrates across an air–liquid interface, the pinch-off of the compound liquid neck arises and the resultant double emulsions moves with tunable lateral displacements in the receiving phase. In the COIS process, the morphology and size of the double emulsions are heavily dependent on the vibration frequency and the inner and outer liquid flow rates. The lateral droplet displacements changing with process parameters can be precisely controlled in experiments and predicted theoretically by the Stokes drift model. Furthermore, the feasibility of the COIS process in spatial gradient drug release is verified. The double emulsions sorted along a specific direction are available for spatial gradient release under thermal and chemical environments, respectively. The COIS technique has great potential in fields of sensors, spatial gradient materials, advanced drug delivery and biomedical applications.